2018
DOI: 10.1029/2018gl078658
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Soil and Plant Interaction by Combining Ground‐Based Quantitative Electromagnetic Induction and Airborne Hyperspectral Data

Abstract: For the first time, we combine depth‐specific soil information obtained from the quantitative inversion of ground‐based multicoil electromagnetic induction data with the airborne hyperspectral vegetation mapping of 1 × 1‐m pixels including Sun‐induced fluorescence (F) to understand how subsurface structures drive above‐surface plant performance. Hyperspectral data were processed to quantitative F and selected biophysical canopy maps, which are proxies for actual photosynthetic rates. These maps showed within‐f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…In mountainous regions, where soil salinity and soil temperature do not vary significantly at the local scale, soil electrical conductivity (soil EC) is often an indicator of the spatial variability of soil thickness, clay content, water content, or some combination of these characteristics (Binley et al, 2015;Miller et al, 2008;Rubin & Hubbard, 2005). Because of the strong influence of these characteristics on plant physiology, studies have found significant correlations between soil EC patterns and leaf area index (LAI; Rudolph et al, 2015), plant photosynthetic activity and growth (von Hebel et al, 2018), and vegetation vigor (Dafflon et al, 2017). The spatially extensive nature of geophysical data allows exploration of how soil properties vary spatially with characteristics such as plant species and dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In mountainous regions, where soil salinity and soil temperature do not vary significantly at the local scale, soil electrical conductivity (soil EC) is often an indicator of the spatial variability of soil thickness, clay content, water content, or some combination of these characteristics (Binley et al, 2015;Miller et al, 2008;Rubin & Hubbard, 2005). Because of the strong influence of these characteristics on plant physiology, studies have found significant correlations between soil EC patterns and leaf area index (LAI; Rudolph et al, 2015), plant photosynthetic activity and growth (von Hebel et al, 2018), and vegetation vigor (Dafflon et al, 2017). The spatially extensive nature of geophysical data allows exploration of how soil properties vary spatially with characteristics such as plant species and dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Geophysical soil sensing to assess soil spatial variability has been documented over the last four decades [17,27,37,42,65,68]. Determining soil variability as affected by human-induced land activities using electromagnetic induction (EMI)-based apparent electrical conductivity (ECa), can effectively discriminate the magnitude of soil variability.…”
Section: Introductionmentioning
confidence: 99%
“…Such systems provide apparent electrical conductivity (σ a ) values that can be used to infer the soil water content distribution within a catchment [1,2], and/or upscale other soil properties [3,4] up to the sub-continental scale [5]. In precision agriculture, σ a patterns help to optimize fertilizer and irrigation application [6,7], to investigate long-term treatment effects [8], to investigate plant and soil interactions [9,10,11,12], and to test the ability of plants to grow in saline soil conditions [13]. The spatial distribution of σ a can also be used to identify buried cables [14], flood embankments [15], and features within morphological, geological, and geoarchaelogical units [16,17,18].…”
Section: Introductionmentioning
confidence: 99%